Policing in contemporary Nigeria: issues and challenges (2013)
The foundation of policing in Nigeria today can be traced to colonial legacy. Colonial policies subjugated the existing traditional informal law enforcement order and forcefully imposed western idea of policing. Thus, policing within the context of oppression and gross misuse of power has been linked to western orientation. This imperial orientation is not only maintained and sustained by successive Nigerian administrations but also have senous implication for an effective policing in Nigeria. This paper identifies critical issues that are germane to policing in contemporary Nigeria. The paper further identifies some challenges that plague the police as an institution in the present democratic era. In spite of pervading problems and consequent challenges, the paper identities prospects in the sustenance of policing in the present democratic dispensation. To achieve this, the paper concludes with good governance in relation to police reform as strategies for an effective policing in Nigeria